The effect of carbamide particles size on morphology and compressive properties foam based magnesium - Fauzi, Muhamad Hazman Ahmad (Universiti Sains Malaysia, 2017)
In this work, the effect of carbamide particles size on morphology and mechanical properties of magnesium and magnesium composite foam containing 1 wt.% alumina were investigated. Magnesium and magnesium composite foam were prepared by powder metallurgy method using sintering dissolution process. The carbamide particle used in this experiment were varied in size; 1.70-2.00 mm, 2.00-2.36 mm, 2.36-2.80 mm and 2.80-3.36 mm. Both of magnesium foams were characterized for morphology, pore size, density, porosity, compressive strength and energy absorption using stereo microscope, densimeter and Instron test. All the pores are distributed homogenously for all the pore sizes for both magnesium and magnesium composite foam. The magnesium foam with carbamide size in the range of 2.00-2.36 showed the highest compressive strength of 6.31 MPa and energy absorption of 11.676 MJ/m3 with an average pore size of 2.17 mm, density of 0.49 g/cm3 and porosity of 72 %. While, magnesium composite foam with carbamide size in the range of 2.00-2.36 also showed the highest compressive strength of 5.094 MPa, energy absorption of 8.975 MJ/m3, density of 0.49 g/cm3 and porosity of 72%. The results showed that carbamide particles size play an important role in determining the compression properties of magnesium and magnesium composite foam by the distribution of carbamide particle size